Perilaku Mahasiswa Universitas Trunojoyo Madura Terhadap Minat Belanja Online di E-Commerce - M. Angkasa Dharu; Qoni'ah Nur Wijayani (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
The use of the internet by students as a means of facilitating their activities and survival through social media has become a trend. The integration between the internet and social networks facilitates online product learning, especially in the context of online shopping. Students' consumption patterns, especially fashion products, have increased in line with their desire to follow the trends of today's young people. Fashion and appearance are the main focus for students, viewing it as an important aspect in showing identity and social status. Students' involvement in using the internet, especially for shopping, has changed their lifestyle significantly. Public consumption trends are influenced by students' online shopping behavior, which is not only based on needs, but also for personal pleasure and lifestyle. This can lead to consumer behavior, where individuals develop purchasing habits to satisfy themselves and increase prestige as a form of demonstrating socio-economic status. E-commerce, as a result of the development of Information Technology systems, has become an important means of meeting consumer needs. Factors such as price, level of trust, time freedom, and product variety influence students' online purchasing intentions. The wide variety of products online is an attraction, while trust is the basis for a mutually beneficial relationship between online sellers and buyers. This research uses a qualitative approach to get an in-depth picture of the impact of e-commerce on student consumption behavior. The research results show that student consumer behavior, especially in terms of online shopping, is influenced by factors such as trust, convenience and security. Trust in e-commerce is a key factor in growing students' buying interest.